Optical and Electrical Properties of Gold-Silver Nanoalloys Synthesized through Photochemical Reduction using Femtosecond Laser - Affi Nur Hidayah; Yuliati Herbani (The Journal of Pure and Applied Chemistry Research, 2020)
In this work we investigated the optical and electrical properties of Au-Ag nanoalloys in various volume ratios. The nanoparticles have been prepared from gold and silver ions reduced by direct irradiation femtosecond  laser. The samples were added into a quartz cuvette and  irradiated for 10 minutes. Each sample was observed the optical property where surface plasmon resonance (SPR) peak was existed. In addition, electrical conductivity of the colloids was derived from the measurement of  the correspond zeta potential by dynamic light scattering (DLS) method. The results showed that the SPR peak of Au-Ag nanoalloy were shifted almost linearly in between 409 nm for Ag and 530 nm for Au depending on their volume fraction. The conductivity measurement showed that Au0Ag100 (pure Ag) nanoparticles has the highest value and Au100Ag0 (pure Au) nanoparticles has the lowest value, and interestingly, Au-Ag nanoalloys have the values between Au0Ag100 and Au100Ag0. Briefly, this work revealed that both optical and electrical properties of Au-Ag nanoalloys can be easily tuned by regulating the volume fraction between the two elements. Keywords: optical properties, electrical properties, Au-Ag nanoalloys, photochemical reduction, femtosecond laser